Should Human Immunodeficiency Virus Specialty Clinics Treat Patients With Hypertension or Refer to Primary Care? An Analysis of Treatment Outcomes. (3rd February 2017) - Appenheimer, A. Ben; Bokhour, Barbara; McInnes, D. Keith; Richardson, Kelly K.; Thurman, Andrew L.; Beck, Brice F.; Vaughan-Sarrazin, Mary; Asch, Steven M.; Midboe, Amanda M.; Taylor, Thom; Dvorin, Kelly; Gifford, Allen L.; et al.
Abstract: Background: Care for people with human immunodeficiency virus (HIV) increasingly focuses on comorbidities, including hypertension. Evidence indicates that antiretroviral therapy and opportunistic infections are best managed by providers experienced in HIV medicine, but it is unclear how to structure comorbidity care. Approaches include providing comorbidity care in HIV clinics ("consolidated care") or combining HIV care with comorbidity management in primary care clinics ("shared care"). We compared blood pressure (BP) control in HIV clinics practicing consolidated care versus shared care. Methods: We created a national cohort of Veterans with HIV and hypertension receiving care in HIV clinics in Veterans Administration facilities and merged these data with a survey asking HIV providers how they delivered hypertension care (5794 Veterans in 73 clinics). We defined BP control as BP ≤140/90 mmHg on the most recent measure. We compared patients' likelihood of experiencing BP control in clinics offering consolidated versus shared care, adjusting for patient and clinic characteristics. Results: Forty-two of 73 clinics (57.5%) practiced consolidated care for hypertension. These clinics were larger and more likely to use multidisciplinary teams. The unadjusted frequency of BP control was 65.6% in consolidated care clinics vs 59.4% in shared care clinics ( P < .01). The likelihood of BP control remained higher for patients in consolidated care clinics after adjusting for patient and clinic characteristics (odds ratio, 1.32; 95% confidence interval, 1.04–1.68). Conclusions: Patients were more likely to experience BP control in clinics reporting consolidated care compared with clinics reporting shared care. For shared-care clinics, improving care coordination between HIV and primary care clinics may improve outcomes.